232k views
24 votes
Use the Distributive Property to solve the equation.

4x - 2(x - 3) = -4 + 5x - 5

show work

User Yaches
by
6.1k points

1 Answer

10 votes

Answer:

x = 5

Explanation:

1. Distributive Property

(Do what's in the parenthesis first)

4x - 2x + 6 = -4 + 5x - 5

2. Combine Like Terms

2x + 6 = -9 + 5x

3. Take away 6 on both sides

2x + 6 - 6 = -9 - 6 +5x

It will give u.....

2x = -15 + 5x

4. Subtract 5x on both sides

2x - 5x = -15

It will give u.....

-3x = -15

5. Divide by -3 on both sides to isolate the variable

-3x / 3 = -15/-3

Now you get....

x = 5

2 negatives make a positive

Thats ur answer

Hope this helped!

User Knowband Plugins
by
6.4k points